SURVEY ON THE EFFECTIVENESS OF ONLINE LECTURES DURING COVID-19 PANDEMIC: METHODS AND DIFFICULTIES - Aristo Hardinata; Halim Simatupang; Fatin Hanifa; Abdul Latip; Shelly Efwinda; Relsas Yogica (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to describe the effectiveness and method of lectures that took place during the Covid-19 pandemic. The Covid-19 pandemic requires all aspects of life to adapt, including in the field of education. This research is a descriptive quantitative study with a simple survey method using an instrument in the form of a google form which was designed to find out what students and lecturers think about lectures during the Covid-19 pandemic. The opinion in question was an opinion about the method or media used as well as the difficulties faced in the implementation of online lectures during the pandemic. This study used a purposive sampling technique, namely 5 universities in Indonesia consisting of 200 lecturers and 200 students. All respondents were asked to fill out an online questionnaire in the form of a google form designed to find out the methods or media used in lectures as well as the difficulties faced in using the media. The survey results show that the combination of media that was mostly used by lecturers and students in lectures is Whatsapp Group, Zoom Meeting, campus E-Learning Website, and Google Classroom. The majority of difficulties experienced by lecturers and students in online implementation are the uneven quality of internet connections. Lecturers find it difficult to psychologically assess students who are attending lectures. Lecturers cannot ensure the seriousness of students in the lecture process. In addition, the lecturer also feels that it takes a lot of time in the matter of using the application or media technically, so it is quite disruptive to the course of lectures such as the slow pace of learning media and the length of time required for students to join in the meeting. Lecturers and students still consider online lectures to be ineffective